Coincidence Points of Weaker Contractions in Partially Ordered Metric Spaces - Kuo-Ching Jen; Ing-Jer Lin; Chi-Ming Chen (Journal of Applied Mathematics)
We prove new coincidence point theorems for the -contractions and generalized Meir-Keeler-type --contractions in partially ordered metric spaces. Our results generalize many recent coincidence point theorems in the literature.